Application of Partial Discharge Critical Monitoring Technology in Internal Defect Detection of Ultra-high Voltage Reactors - ZHAO Lin; SHAO Xianjun; JIN Yongtao; YANG Yong; YANG Zhi; ZHENG Wenzhe (Zhejiang dianli, 2022)
Two cases of abnormal acetylene content rise in the oil chromatogram of ultra-high voltage reactors are introduced in this paper. To monitor the internal condition of the reactor in real time and judge the type of defect， a partial discharge critical monitoring device is used for long-term monitoring. Critical monitoring results in case 1 show that there is a partial discharge caused by floating potential and weak insulation defects inside the reactor that lead to the rapid content rise of acetylene. Critical monitoring results in case 2 show that the intermittent partial discharge signal inside the reactor is an external interference signal near the north side of the ultra-high voltage reactors， and there is no obvious internal discharge signal. As to the iron core clamp ground current test， the internal defect type is the high temperature and overheating gas produced by the multi-point grounding of the magnetic circuit， and the chromatogram growth has nothing to do with the partial discharge. It is discovered by disassembly that the equipotential copper tape of the ground screen connected to the clamp on reactor body 1 in case 1 has broken discharge traces and the insulation paperboard is damaged. In case 2， the iron yoke of reactor body 1 and the magnetic shield of the upper body are overlapped， and the contact surface is obviously ablated with no obvious discharge trace inside， which excludes the possibility of internal discharge. The disassembly results are consistent with the analysis conclusions of the partial discharge critical monitoring system， verifying the effectiveness of the partial discharge critical monitoring method in power equipment defect analysis. The method can evade misjudgment due to external signal interference.